Polymer electrolyte membrane and method for manufacturing membrane-electrode assembly
By performing solvent treatment and hot pressing on the polymer electrolyte membrane, its physical defects are removed and a catalyst layer is formed on a uniform surface, the interface peeling problem caused by polymer electrolyte membrane defects in fuel cells is solved, and the cell performance and stability are improved.
Patent Information
- Application Number
- CN202380056617.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-13
- Publication Date
- 2025-03-18
AI Technical Summary
In fuel cells, physical defects in the polymer electrolyte membrane lead to the interface peeling between the catalyst layer and the membrane, increasing the interface resistance between the membrane-electrode and reducing the cell performance.
The polymer electrolyte membrane with physical defects is swelled by solvent treatment, and heat and pressure are applied after swelling to remove surface defects and form a uniform surface. The catalyst layer is then coated on the polymer electrolyte membrane on the uniform surface.
This method effectively reduces the interface resistance between the polymer electrolyte membrane and the electrode, improves the cell performance of the membrane-electrode assembly, and enhances the physical stability under long-term operation.
Smart Images

Figure CN119654722A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a polymer electrolyte membrane and a membrane-electrode assembly capable of controlling the surface of a polymer electrolyte membrane having physical defects to be uniform. Background Art
[0002] A fuel cell is a battery with a power generation system that directly converts the energy of a chemical reaction (such as the oxidation / reduction reaction of hydrogen and oxygen included in hydrocarbon fuel materials such as methanol, ethanol, and natural gas) into electrical energy. Fuel cells have attracted much attention as the next generation of clean energy that can replace fossil energy due to their high energy efficiency and low pollutant emissions.
[0003] This fuel cell has a stack structure made by stacking unit cells and has the advantage of being able to produce a wide range of outputs. In addition, since the energy density of this fuel cell is four to ten times that of a small lithium battery, it has attracted attention as a small and mobile portable power source.
[0004] The stack that actually generates electricity in a fuel cell has a structure of several or dozens of unit cells stacked together, wherein the unit cells are composed of a membrane-electrode assembly (MEA) and a separator (also called a bipolar plate). The membrane-electrode assembly is generally constructed to have an oxidation electrode (Anode, or fuel electrode) and a reduction electrode (Cathode, or air electrode) formed on both sides of the electrolyte membrane with an electrolyte membrane.
[0005] In addition, there are two major methods for manufacturing membrane-electrode assemblies used in fuel cells. First, the CCS (Catalyst Coated Substrate) method is a method of coating a catalyst layer on a substrate, and the CCM (Catalyst Coated Membrane) method is a method of forming a catalyst layer on a polymer electrolyte membrane.
[0006] The CCM method is divided into two methods. The first is a method of directly coating the catalyst layer on the polymer electrolyte membrane (Direct Coating), and the second is a method of first forming the catalyst layer on the substrate and then transferring the catalyst layer to the polymer electrolyte membrane using heat and pressure.
[0007] When forming a catalyst layer on a polymer electrolyte membrane, the properties of the polymer electrolyte membrane surface are an important requirement to be considered when transferring electrodes. If a polymer electrolyte membrane with sulfonic acid functional groups is subjected to a transfer process at a high temperature and pressure while the surface of the membrane is uneven due to defects, the interface between the catalyst layer and the polymer electrolyte membrane will peel off, the interface resistance between the membrane and the electrode will increase, and the performance will decrease. Summary of the invention
[0008] An implementation example provides a method for manufacturing a polymer electrolyte membrane, which can prevent the polymer electrolyte membrane from deteriorating while controlling the surface of the polymer electrolyte membrane with physical defects to be uniform, thereby reducing the interface resistance between the polymer electrolyte membrane and the electrode, obtaining excellent battery cell performance and improving the physical stability of MEA under long-term operation.
[0009] Another implementation example provides a method for manufacturing a membrane-electrode assembly using the manufactured polymer electrolyte membrane.
[0010] According to an implementation example, a method for manufacturing a polymer electrolyte membrane is provided, which includes: applying a solvent to a polymer electrolyte membrane having defects on its surface to swell the polymer electrolyte membrane; and applying heat and pressure to the swollen polymer electrolyte membrane.
[0011] The solvent may include water, alcohol, an organic solvent, or a combination thereof.
[0012] The solvent may be a mixed solvent including more than 0 wt % and less than 100 wt % of water and more than 0 wt % and less than 100 wt % of alcohol.
[0013] The method of applying the solvent to the polymer electrolyte membrane may include spraying, steam spraying, or a combination thereof.
[0014] The swelling step may be performed for 1 second to 30 seconds.
[0015] The length of the polymer electrolyte membrane after swelling may increase by 1% to 20% compared with the length before swelling.
[0016] The thickness of the polymer electrolyte membrane after swelling may increase by 1% to 20% compared with the thickness before swelling.
[0017] The step of applying heat and pressure may be performed for 1 second to 30 seconds.
[0018] The step of applying heat and pressure may be performed at a temperature of about 20% of the intrinsic glass transition temperature (Tg) of the polymer electrolyte membrane.
[0019] The step of applying heat and pressure may be performed at a temperature of 110°C to 130°C.
[0020] The step of applying heat and pressure may be performed by applying 50 kg / cm 2 Up to 200kg / cm 2 pressure to carry out.
[0021] The degree of degradation of the hydrogen ion conductivity of the polymer electrolyte membrane before and after the step of applying heat and pressure may be less than 5%.
[0022] According to another implementation example, a method for manufacturing a membrane-electrode assembly is provided, which includes the step of coating a composition for forming a catalyst layer on one or both surfaces of a polymer electrolyte membrane manufactured by the above method.
[0023] According to a method for manufacturing a polymer electrolyte membrane in an implementation example, the polymer electrolyte membrane can be prevented from deteriorating while the surface of the polymer electrolyte membrane with physical defects can be controlled to be uniform, thereby reducing the interface resistance between the polymer electrolyte membrane and the electrode, obtaining excellent battery cell performance and improving the physical stability of MEA under long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a diagram showing a manufacturing process of a membrane-electrode assembly according to an implementation example.
[0025] Figure 2 It is a diagram showing a manufacturing process of a membrane-electrode assembly according to the conventional technology.
[0026] Figure 3 These are photographs of a polymer electrolyte membrane having surface defects and a polymer electrolyte membrane in which surface defects are controlled in Example 1.
[0027] Figure 4 This is a graph showing the swelling ratio of the polymer electrolyte membrane used for controlling surface defects in Example 1 at different solvent spraying amounts per unit area.
[0028] Figure 5 This is a graph showing the swelling ratio of the polymer electrolyte membrane used for controlling surface defects in Example 1 at different water-alcohol solvent ratios.
[0029] Figure 6 This is a graph showing the drying rate of the polymer electrolyte membrane used for controlling surface defects in Example 1 with changes in hot pressing time.
[0030] Figure 7 is a scanning electron microscope (SEM) photograph of the membrane-electrode assembly manufactured in Example 1.
[0031] Figure 8 is a scanning electron microscope (SEM) photograph of the membrane-electrode assembly manufactured in Comparative Example 1.
[0032] Fig. 9 : is a current density-voltage graph of the membrane-electrode assemblies manufactured in Example 1 and Comparative Example 1.
[0033] Fig.10 3 is a graph of potential-current density of the membrane-electrode assemblies manufactured in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0034] The advantages and features of the technology to be described later and the methods for implementing them will become clear if reference is made to the implementation examples described in detail later in conjunction with the accompanying drawings. However, the form of implementation is not limited to the implementation examples disclosed below. Unless otherwise defined, all terms (including technical and scientific terms) used in this specification can be used as meanings commonly understood by people with general knowledge in the relevant technical field. In addition, terms defined in generally used dictionaries should not be interpreted ideally or excessively unless explicitly defined. Throughout the specification, when a part "includes" a certain structural element, unless there is a special record to the contrary, this means that other structural elements may be further included, rather than excluding other structural elements.
[0035] Furthermore, unless otherwise specified in a sentence, a singular form also includes a plural form.
[0036] A method for producing a polymer electrolyte membrane according to an implementation example includes: a step of swelling the polymer electrolyte membrane; and a step of applying heat and pressure to the swollen polymer electrolyte membrane.
[0037] The polymer electrolyte membrane includes an ion conductor. The ion conductor may be a cation conductor having a cation exchange group capable of transferring cations such as protons, or an anion conductor having an anion exchange group capable of transferring anions such as hydroxide ions, carbonate or bicarbonate.
[0038] The cation exchange group may be any one selected from the group consisting of a sulfonic acid group, a carboxyl group, a boric acid group, a phosphoric acid group, an imide group, a sulfonimide group, a sulfonamide group, and a combination thereof, and may generally be a sulfonic acid group or a carboxyl group.
[0039] Cationic conductors include cation exchange groups, and examples include: fluorine-containing polymers with fluorine in the main chain; hydrocarbon polymers such as benzimidazole, polyamide, polyamideimide, polyimide, polyacetal, polyethylene, polypropylene, acrylic resin, polyester, polysulfone, polyether, polyetherimide, polyester, polyethersulfone, polyetherimide, polycarbonate, polystyrene, polyphenylene sulfide, polyetheretherketone, polyetherketone, polyarylethersulfone, polyphosphazene or polyphenylquinoxaline; partially fluorinated polymers such as polystyrene-graft-ethylenetetrafluoroethylene copolymer or polystyrene-graft-polytetrafluoroethylene copolymer; sulfonimide, etc.
[0040] More specifically, when the cation conductor is a hydrogen ion cation conductor, the polymer may include a cation exchange group selected from sulfonic acid groups, carboxylic acid groups, phosphoric acid groups, phosphonic acid groups and their derivatives on the side chain, and specific examples thereof include: fluorine-based polymers including poly(perfluorosulfonic acid), poly(perfluorocarboxylic acid), copolymers of tetrafluoroethylene and fluorovinyl ether including sulfonic acid groups, defluorinated sulfide polyether ketone or mixtures thereof; hydrocarbon polymers including sulfonated polyimide (S-PI), sulfonated polyarylethersulfone (S-PAES), sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (SPBI), sulfonated polysulfone (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyquinoxaline (S-PS), sulfonated polyphosphazene, sulfonated polyoxoline (S-PS), sulfonated polyoxocyanate (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyoxocyanate (S-PS), sulfonated polyoxocyanate (S-PSU), ... The present invention relates to polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene oxide, sulfonated polyether sulfone, sulfonated polyether ketone, sulfonated polyphenylenesulfone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylene ether, sulfonated polyarylene ether nitrile, sulfonated polyarylene ether ether nitrile, polyarylene ether sulfone ketone, and mixtures thereof, but are not limited thereto.
[0041] Anion conductors are polymers that can transport anions such as hydroxide, carbonate or bicarbonate. The hydroxide or halide (usually chloride) forms of anion conductors are commercially available. Anion conductors can be used in industrial water purification, metal separation or catalyst processes.
[0042] As anion conductors, polymers doped with metal hydroxides can generally be used, and specifically poly(ether sulfone), polystyrene, vinyl polymers, poly(vinyl chloride), poly(vinylidene fluoride), poly(tetrafluoroethylene), poly(benzimidazole) or poly(ethylene glycol) doped with metal hydroxides can be used.
[0043] Furthermore, as the polymer electrolyte membrane, a fluorine-based polymer electrolyte membrane mainly composed of a fluorine-based ion conductor can be mainly used, but a hydrocarbon-based polymer electrolyte membrane mainly composed of a hydrocarbon-based ion conductor can also be used.
[0044] The polymer electrolyte membrane may have defects on its surface. The defects may be physical defects, such as wrinkles, cracks, depressions, tears, grooves, surface irregularities, etc. caused by folding.
[0045] If a catalyst layer is formed on such a polymer electrolyte membrane having surface defects, the interface between the catalyst layer and the membrane will be peeled off, thereby increasing the interface resistance between the membrane and the electrode and degrading the performance.
[0046] In order to control the surface of the polymer electrolyte membrane with physical defects to be uniform, the method for manufacturing the polymer electrolyte membrane according to one embodiment includes a pretreatment process, that is, before applying the composition for forming a catalyst layer on the polymer electrolyte membrane, applying a solvent to the polymer electrolyte membrane to swell the polymer electrolyte membrane.
[0047] As a solvent for swelling the polymer electrolyte membrane, any solvent can be used as long as it can expand the hydrophilic chains and hydrophobic chains of the polymer electrolyte membrane and swell the polymer electrolyte membrane having hydrophilic channels in all directions. For example, the solvent may include water, alcohol, organic solvent or a combination thereof.
[0048] The alcohol may include n-propanol (NPA), isopropanol (IPA), ethanol (EtOH) or a mixture thereof, and the organic solvent may include N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), tetrahydrofuran (THF) or a mixture thereof.
[0049] The solvent used to swell the polymer electrolyte membrane can be appropriately selected and mixed according to the type of polymer electrolyte membrane, and the mixing ratio can also be appropriately adjusted according to the type of polymer electrolyte membrane. For example, the mixed solvent may include water and alcohol greater than 0% by weight and less than 100% by weight or 25% to 75% by weight. For reference, when the same amount of solvent is used, the swelling rate when the composition of the mixed solvent is 100% by weight of alcohol is higher than the swelling rate when the composition of the mixed solvent is 100% by weight of water.
[0050] As a method of applying a solvent to the polymer electrolyte membrane, the polymer electrolyte membrane may be loaded or immersed in the solvent, or the solvent may be applied to one or both sides of the polymer electrolyte membrane. When applying the solvent, a method including spraying, steam spraying, rod coating, comma coating, slot coating, screen printing, blade coating, lamination or a combination thereof may be used.
[0051] The time for swelling the polymer electrolyte membrane can be appropriately adjusted according to the type of solvent, for example, 1 second to 30 seconds. When the swelling time is shorter than 1 second, the expansion of the hydrophilic channels in the polymer surface may not be achieved, and when it exceeds 30 seconds, the expansion of the hydrophilic channels may be too large, thereby causing the original morphology to be deformed.
[0052] The length of the polymer electrolyte membrane after swelling can increase by 1% to 20% compared to the length before swelling, for example, it can increase by 3% to 15%. In addition, the thickness of the polymer electrolyte membrane after swelling can increase by 1% to 20% compared to the thickness before swelling, for example, it can increase by 3% to 15%.
[0053] The swelling ratio of the polymer electrolyte membrane in the longitudinal direction or the thickness direction may vary depending on the type and amount of the solvent used and the type and thickness of the polymer electrolyte membrane.
[0054] The length direction of the polymer electrolyte membrane refers to the plane direction perpendicular to the thickness direction, and can represent either or both of the machine direction (MD) and the transverse direction (TD). In this case, the machine direction refers to the direction in which the rolls travel when the polymer electrolyte membrane is continuously produced by a roll-to-roll method or the direction in which the manufactured polymer electrolyte membrane is wound.
[0055] The swelling ratio (%) can be calculated by (size after swelling - size before swelling) / size before swelling×100.
[0056] The spraying amount of the solvent for swelling the polymer electrolyte membrane can be appropriately adjusted according to the mixed composition of the solvent, and can be, for example, 0.4 mg / cm 2 Up to 6.8mg / cm 2 injection.
[0057] When the swelling ratio is less than 1%, the expansion of the hydrophilic channels in the polymer surface may not be achieved, and when the swelling ratio is greater than 20%, the expansion of the hydrophilic channels is too large, which may cause the original morphology to be deformed. Therefore, the swelling ratio can be adjusted to a level of 1% to 20%.
[0058] Then, heat and pressure are applied to the swollen polymer electrolyte membrane.
[0059] In the step of applying heat and pressure, the swollen polymer electrolyte membrane can be controlled by instantaneous heat and pressure, thereby preventing the polymer electrolyte membrane from being deteriorated. That is, when instantaneous heat and pressure are applied, the generated steam exists in the space between the press and the membrane, thereby preventing the polymer electrolyte membrane from being deteriorated by the Leidenfrost effect.
[0060] Thus, the step of applying heat and pressure may be performed for 1 second to 30 seconds, for example, for 1 second to 10 seconds.
[0061] When the hot pressing time for applying heat and pressure is shorter than 1 second, sufficient heat transfer cannot be achieved, and thus the drying rate may not reach 100%. When the hot pressing time exceeds 30 seconds, depending on the heat treatment temperature, degradation of the polymer electrolyte membrane may occur, which may cause cross-linking between polymer chains, thereby reducing performance.
[0062] The step of applying heat and pressure can be performed at a temperature of about 20% of the inherent glass transition temperature (Tg) of the polymer electrolyte membrane. Thus, heat and pressure can be simultaneously transmitted according to the inherent characteristic glass transition temperature (Tg) of the polymer electrolyte membrane, thereby controlling the surface of the polymer electrolyte membrane with physical defects to be uniform.
[0063] For example, the temperature at which heat and pressure are applied may be 110° C. to 130° C., or may be 115° C. to 125° C. When the temperature at which heat and pressure are applied is lower than 110° C., the polymer chain cannot be changed due to the heat having a temperature below the glass transition temperature, and when the temperature exceeds 130° C., the polymer electrolyte membrane may be degraded and the surface and the inside of the membrane may be solidified.
[0064] The step of applying heat and pressure may be performed by applying 50 kg / cm 2 Up to 200kg / cm 2 When the pressure of heat and pressure is less than 50kg / cm 2 When the pressure exceeds 200 kg / cm 2When the temperature is too high, the polymer electrolyte membrane may be degraded and the membrane thickness may change.
[0065] Before and after the step of applying heat and pressure, the degree of deterioration of the hydrogen ion conductivity of the polymer electrolyte membrane may be less than 5%, for example, preferably less than 2%. The method of measuring the hydrogen ion conductivity of the polymer electrolyte membrane is not particularly limited in the present invention, and the hydrogen ion conductivity of the polymer electrolyte membrane before and after the step of applying heat and pressure only needs to be measured in the same method and under the same conditions. When the degree of deterioration of the polymer electrolyte membrane is more than 5%, it is difficult to fully transfer hydrogen ions, which may cause the performance of the fuel cell to decrease.
[0066] In addition, the method for producing the polymer electrolyte membrane may further include the step of mechanically stretching the polymer electrolyte membrane. When the surface defects of the polymer electrolyte membrane cannot be sufficiently controlled by simply applying heat and pressure to the polymer electrolyte membrane, the defects may be further controlled by mechanical stretching.
[0067] As an example, mechanical stretching can be performed by applying tension in the machine direction (MD) while transferring the polymer electrolyte membrane using a roll-to-roll device, and tension can be applied not only in the machine direction but also in the transverse direction (TD) perpendicular to the machine direction.
[0068] According to another embodiment, a method for manufacturing a membrane-electrode assembly includes the step of applying a composition for forming a catalyst layer on one or both surfaces of a polymer electrolyte membrane having controlled surface defects.
[0069] Figure 1 is a diagram showing a manufacturing process of a membrane-electrode assembly according to another implementation example, Figure 2 It is a diagram showing a manufacturing process of a membrane-electrode assembly according to the conventional technology.
[0070] Reference Figure 2 If the transfer process (S2) is performed at a relatively high temperature and pressure to form the catalyst layers 30, 30' when the surface of the polymer electrolyte membrane 51 is uneven, the interface 52 between the catalyst layers 30, 30' and the polymer electrolyte membrane 51 will peel off, thereby increasing the interface resistance between the membrane and the electrode and reducing the performance.
[0071] On the contrary, if Figure 1As shown, a solvent 11 is applied to a polymer electrolyte membrane 51 having defects on the surface by using a sprayer 10 or the like to swell the polymer electrolyte membrane 51, and instantaneous heat and pressure 20 (S1) are applied to the swollen polymer electrolyte membrane 51, thereby preventing the polymer electrolyte membrane 50 from deteriorating and controlling the surface to be uniform. Then, if a catalyst layer 30, 30' (S2) is formed on the surface of the polymer electrolyte membrane 50 whose surface is controlled to be uniform, the interface resistance between the polymer electrolyte membrane and the electrode can be reduced, thereby achieving excellent cell performance and improving the physical stability of the MEA under long-term operation.
[0072] The composition for forming the catalyst layer can be produced by combining a catalyst, an ionomer, and a solvent.
[0073] As the catalyst, any substance can be used as long as it can be used as a catalyst in the hydrogen oxidation reaction and the oxygen reduction reaction, but a platinum group metal is preferably used.
[0074] The platinum group metal may include one selected from platinum (Pt), palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), platinum-M alloy (M is one or more selected from palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), gallium (Ga), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), silver (Ag), gold (Au), zinc (Zn), tin (Sn), molybdenum (Mo), tungsten (W), lanthanum (La) and rhodium (Rh)), non-platinum alloys and combinations thereof. More preferably, a combination of two or more metals selected from the platinum group catalyst metal group can be used, but it is not limited to this. As long as it is a platinum group catalyst metal that can be used in the present technical field, it can be used without restriction.
[0075] Specifically, the platinum alloy can use one selected from Pt-Pd, Pt-Sn, Pt-Mo, Pt-Cr, Pt-W, Pt-Ru, Pt-Ni, Pt-Ru-W, Pt-Ru-Ni, Pt-Ru-Mo, Pt-Ru-Rh-Ni, Pt-Ru-Sn-W, Pt-Ru-Ir-Ni, Pt-Co, Pt-Co-Mn, Pt-Co-Ni, Pt-Co-Fe, Pt-Co-Ir, Pt-Co-S, Pt-Co-P, Pt-Fe, Pt-Fe-Ir, Pt-Fe-S, Pt-Fe-P, Pt-Au-Co, Pt-Au-Fe, Pt-Au-Ni, Pt-Ni, Pt-Ni-Ir, Pt-Cr, Pt-Cr-Ir and combinations thereof, or can use a mixture of two or more thereof.
[0076] In addition, the non-platinum alloy can use one selected from Ir-Fe, Ir-Ru, Ir-Os, Co-Fe, Co-Ru, Co-Os, Rh-Fe, Rh-Ru, Rh-Os, Ir-Ru-Fe, Ir-Ru-Os, Rh-Ru-Fe, Rh-Ru-Os, Fe-N, Fe-P, Co-N and combinations thereof, or can use a mixture of two or more.
[0077] In addition, the catalyst may be a metal itself (black) or a catalyst metal supported on a carrier.
[0078] The carrier can be selected from carbon-based carriers, porous inorganic oxides such as zirconium oxide, aluminum oxide, titanium oxide, silicon oxide, cerium oxide, etc., zeolite, etc. The carbon-based carrier can be selected from graphite, super P, carbon fiber, carbon sheet, carbon black, Ketjen Black, superconductive acetylene black (Denkablack), acetylene black, carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, activated carbon, carbon nanofiber, carbon nanowire, carbon nanosphere, carbon nanohorn, carbon nanocage, carbon nanoring, ordered nanoporous carbon (ordered nano- / meso-porous carbon), carbon aerogel, mesoporous carbon, graphene, stabilized carbon, activated carbon and a combination of more than one of them, but is not limited thereto, and any carrier that can be used in the technical field can be used without restriction.
[0079] The catalyst may be located on the surface of the carrier, or may enter the interior of the carrier while filling the internal pores of the carrier.
[0080] When a noble metal loaded on a carrier is used as a catalyst, a commercially available product that has been commercially used can be used, or the noble metal can be loaded on a carrier for manufacture and use. The process of loading a noble metal on a carrier is well known in the art, so even if a detailed description is omitted in this specification, it can be easily understood by those engaged in the art.
[0081] The composition for forming the catalyst layer may include 20 to 80 weight % of the catalyst based on the total weight of the catalyst layer. When the content of the catalyst contained is less than 20 weight % of the total weight of the catalyst layer, the activity may be reduced. When it is greater than 80 weight %, the active area may be reduced due to the aggregation of the catalyst, which may lead to a decrease in the activity of the catalyst.
[0082] The composition for forming the catalyst layer includes an ion conductor in order to improve the adhesion of the catalyst and to transfer hydrogen ions. The ionomer used as a typical polymer ion conductor may be one selected from fluorine-based ionomers, hydrocarbon-based ionomers, and mixtures thereof.
[0083] Fluorine-based ionomers have cation exchange groups that can transfer cations such as protons or anion exchange groups that can transfer anions such as hydroxide ions, carbonates or bicarbonates, and can be listed as: fluorine-based polymers containing fluorine in the main chain; or partially fluorinated polymers such as polystyrene-grafted-ethylene tetrafluoroethylene copolymers or polystyrene-grafted-polytetrafluoroethylene copolymers, and specific examples can be fluorine-based polymers including poly (perfluorosulfonic acid), poly (perfluorocarboxylic acid), copolymers of tetrafluoroethylene and fluorovinyl ether including sulfonic acid groups, defluorinated sulfurized polyether ketones or mixtures thereof. The cation exchange group can be one selected from sulfonic acid groups, carboxyl groups, boric acid groups, phosphoric acid groups, imide groups, sulfonimide groups, sulfonamide groups and combinations thereof, and can generally be sulfonic acid groups or carboxyl groups. In addition, fluorine-based ionomers can be used alone, or two or more can be mixed and used.
[0084] In addition, the hydrocarbon ionomer has a cation exchange group capable of transferring cations such as protons or an anion exchange group capable of transferring anions such as hydroxide ions, carbonates or bicarbonates, and may be a polymer including a hydrocarbon polymer such as imidazole, benzimidazole, polyamide, polyamideimide, polyimide, polyacetal, polyethylene, polypropylene, acrylic resin, polyester, polysulfone, polyether, polyetherimide, polyester, polyethersulfone, polyetherimide, polycarbonate, polystyrene, polyphenylene sulfide, polyetheretherketone, polyetherketone, polyarylethersulfone, polyphosphazene or polyphenylquinoxaline in the main chain. Specific examples include sulfonated polyimide (S-PI), sulfonated polyarylethersulfone (S-PAES), sulfonated polyetheretherketone (SPEEK), sulfonated polybenzimidazole (sulfonated polybenzimidazole, SPBI), sulfonated polysulfone (S-PSU), sulfonated polystyrene (S-PS), sulfonated polyphosphazene, sulfonated polyquinoxaline, sulfonated polyketone, sulfonated polyphenylene oxide, sulfonated polyether sulfone, sulfonated polyether ketone, sulfonated polyphenylene sulfone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfidesulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylene ether, sulfonated polyarylene ether nitrile, sulfonated polyarylene ether ether nitrile, polyarylene ether sulfone ketone The hydrocarbon polymers include, but are not limited to, sulfone, ketone, and mixtures thereof. In addition, the hydrocarbon ionomers may be used alone or in combination of two or more.
[0085] In the composition for forming the catalyst layer, 20 to 45 weight % of the ionomer may be included, specifically, 25 to 38 weight % of the ionomer may be included, based on the total weight of the catalyst layer. When the content of the ionomer is less than 20 weight % of the total weight of the catalyst layer, the performance of the fuel cell may be reduced, and when it exceeds 45 weight %, due to the excessive amount of ionomer, agglomeration between ionomers may occur.
[0086] The solvent may be a solvent selected from water, a hydrophilic solvent, an organic solvent, and a mixture of more than one thereof.
[0087] The hydrophilic solvent may be a solvent having one or more functional groups selected from alcohols, ketones, aldehydes, carbonates, carboxylates, carboxylates, ethers and amides including a linear, branched, saturated or unsaturated hydrocarbon having 1 to 12 carbon atoms as the main chain, and these functional groups may include an alicyclic compound or an aromatic ring compound as at least a part of the main chain. As a specific example, alcohols include methanol, ethanol, isopropanol, ethoxyethanol, n-propanol, butanol, 1,2-propylene glycol, 1-pentanol, 1,5-pentanediol, 1,9-nonanediol, etc.; ketones include heptanone, octanone, etc.; aldehydes include benzaldehyde, tolualdehyde, etc.; esters include methyl valerate, ethyl 2-hydroxypropionate, etc.; carboxylic acids include valeric acid, heptanoic acid, etc.; ethers include methoxybenzene, dimethoxypropane, etc.; amides include propionamide, butyramide, dimethylacetamide, etc.
[0088] The organic solvent may be selected from N-methylpyrrolidone, dimethyl sulfoxide, tetrahydrofuran and mixtures thereof.
[0089] Relative to the total weight of the composition for forming the catalyst layer, it may contain 80 wt % to 95 wt % of solvent. When the solvent content is less than 80 wt %, the solid content is too high, and when the catalyst layer is coated, it may be difficult to disperse due to cracking and high viscosity. When the solvent content is greater than 95 wt %, it may be detrimental to the activity of the catalyst layer.
[0090] The catalyst layer is formed by applying the produced catalyst layer forming composition onto the surface of the polymer electrolyte membrane or the substrate.
[0091] When the catalyst layer forming composition is directly coated on the polymer electrolyte membrane, the catalyst layer forming composition in which the catalyst is dispersed may be continuously or intermittently transferred to a coater and then uniformly coated on the polymer electrolyte membrane to a predetermined thickness.
[0092] In more detail, depending on the viscosity of the composition used to form the catalyst layer, it can be continuously transferred to a coating machine such as a die, gravure, bar, or comma coater by a pump, and then coated using a slit coating, rod coating, comma coating, screen printing, spraying, blade coating, brush coating, or the like.
[0093] Finally, the polymer electrolyte membrane coated with the composition for forming a catalyst layer is dried. Through the drying process, the solvent remaining in the coated composition for forming a catalyst layer and the polymer electrolyte membrane is removed.
[0094] Drying can be carried out by various drying methods such as hot air drying, vacuum drying, infrared (IR) drying, etc. The drying temperature and time can be appropriately adjusted according to the boiling point (BP) of the solvent used. Specifically, the drying can be carried out at a drying temperature of 60°C to 150°C for 0.5 to 10 hours.
[0095] The specific embodiments of the present invention are presented below. However, the embodiments described below are only for the purpose of specifically illustrating or explaining the embodiments of the present invention, and the present invention is not limited thereto. In addition, the contents not described here are contents that can be fully deduced technically by those familiar with the technical field, so their description is omitted.
[0096] [Manufacturing Example: Manufacture of a membrane-electrode assembly]
[0097] (Example 1)
[0098] At room temperature, 0.4 mg / cm per unit area 2 The amount of Figure 3 A mixture of n-propanol (NPA) and water (50:50 wt.%) was sprayed on the surface of a polymer electrolyte membrane (NRE211, DuPont Co., USA) having physical defects on the surface as shown in the figure for two seconds to swell the polymer electrolyte membrane at a thickness direction swelling rate of 5%.
[0099] The membrane was placed in an oven preheated to 120°C, the glass transition temperature (Tg) of the polymer electrolyte membrane, and heated at 120 kg / cm 2 The polymer electrolyte membrane is pressed with a pressure of 1000 μm for two seconds to remove surface defects.
[0100] The catalyst loading of the anode electrode is Pt / C catalyst 0.15 mgPt / cm 2 , and was manufactured by a decal method. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0101] The catalyst loading of the cathode electrode is Pt / C catalyst 0.35 mgPt / cm 2 , and was manufactured by transfer printing. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0102] After an anode electrode and a cathode electrode were placed on both sides of a polymer electrolyte membrane with controlled surface defects, a membrane-electrode assembly (MEA) was manufactured at a pressure of 30 bar and 150° C. for 10 minutes.
[0103] (Example 2)
[0104] Will be like Figure 3 A polymer electrolyte membrane (NRE211, DuPont Co., USA) with physical defects on the surface as shown in the figure was placed in a roll-to-roll system and heated to 0.4 mg / cm per unit area. 2 A mixed solution of n-propanol (NPA) and water (50:50 wt.%) was steam-sprayed in an amount of 1000 rpm for 2 seconds to swell the polymer electrolyte membrane at a thickness-direction swelling ratio of 8%.
[0105] The polymer electrolyte membrane was passed through a roll preheated to a glass transition temperature (Tg) of 120°C and heated at 120 kg / cm 2 The polymer electrolyte membrane is pressed with a pressure of 1000 μm for two seconds to remove surface defects.
[0106] The catalyst loading of the anode electrode is Pt / C catalyst 0.15 mgPt / cm 2 , and was manufactured by a decal method. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0107] The catalyst loading of the cathode electrode is Pt / C catalyst 0.35 mgPt / cm 2 , and was manufactured by transfer printing. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0108] After an anode electrode and a cathode electrode were placed on both sides of a polymer electrolyte membrane with controlled surface defects, a membrane-electrode assembly (MEA) was manufactured at a pressure of 30 bar and 150° C. for 10 minutes.
[0109] (Comparative Example 1)
[0110] The catalyst loading of the anode electrode is Pt / C catalyst 0.15 mgPt / cm 2 , and was manufactured by a decal method. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0111] The catalyst loading of the cathode electrode is Pt / C catalyst 0.35 mgPt / cm 2, and was manufactured by transfer printing. Nafion ionomer (5 wt % Nafion Dispersion, DuPont Co., USA) was used, and the ionomer / carbon ratio was 0.9.
[0112] After an anode electrode and a cathode electrode were placed on both sides of a polymer electrolyte membrane (NRE211, DuPont Co., USA) having physical defects on the surface, the membrane-electrode assembly (MEA) was manufactured at a pressure of 30 bar and 150° C. for 10 minutes.
[0113] [Experimental Example 1: Measurement of changes in swelling rate and drying rate under changing process conditions]
[0114] When the solvent injection amount was changed in Example 1, the change in the swelling ratio in the thickness direction of the polymer electrolyte membrane was measured, and the results are shown in FIG. Figure 4 middle.
[0115] from Figure 4 It is found that, in both the case where the solvent is water and the case where the solvent is alcohol, the swelling ratio in the thickness direction of the polymer electrolyte membrane increases as the amount of solvent sprayed increases.
[0116] In addition, when the solvent ratio was changed in Example 1, the change in the swelling ratio in the thickness direction of the polymer electrolyte membrane was measured, and the results are shown in FIG. Figure 5 middle.
[0117] from Figure 5 It is understood that when the same amount of solvent is used, the swelling ratio when the mixed solvent composition is 100 wt % of alcohol is higher than the swelling ratio when the mixed solvent composition is 100 wt % of water.
[0118] In addition, the drying rate of the polymer electrolyte membrane when the hot pressing time was changed in Example 1 was measured, and the results are shown in FIG. Figure 5 middle.
[0119] from Figure 5 It is known that the drying rate of the polymer electrolyte membrane increases with the increase in the hot pressing time, and when the hot pressing time for applying heat and pressure is one second or longer, sufficient heat transfer is achieved, so that the drying rate approaches 100%.
[0120] [Experimental Example 2: Interface Measurement of Membrane-Electrode Assembly]
[0121] Scanning electron microscope (SEM) photographs of the interface between the polymer electrolyte membrane and the catalyst layer of the membrane-electrode assembly manufactured in Example 1 and Comparative Example 1 are respectively shown. Figure 7 and Figure 8 middle.
[0122] Reference Figure 7 and Figure 8 It can be seen that the membrane-electrode assembly manufactured in Example 1 forms a catalyst layer after controlling surface defects, so that the interface between the polymer electrolyte membrane and the electrode is flat and the interface resistance is low; on the contrary, the membrane-electrode assembly manufactured in Comparative Example 1 is manufactured using a polymer electrolyte membrane with surface defects, so the interface between the polymer electrolyte membrane and the electrode is uneven, and the interface between the catalyst layer and the polymer electrolyte membrane is peeled off, so that the interface resistance between the membrane and the electrode increases and the performance decreases.
[0123] [Experimental Example 3: Performance Evaluation of Membrane-Electrode Assembly]
[0124] The performance of the membrane-electrode assemblies manufactured in Example 1 and Comparative Example 1 was measured and the results are shown in Fig. 9 and Fig.10 middle.
[0125] Fig. 9 is a current density-voltage graph of the membrane-electrode assemblies manufactured in Example 1 and Comparative Example 1, Fig.10 3 is a graph of potential-current density of the membrane-electrode assemblies manufactured in Example 1 and Comparative Example 1.
[0126] The cell voltage (voltage, V) is at a cell temperature of 65°C, SR (A / C) of 1.5 / 2.0, RH (A / C) of 100 / 100 (%), and operating pressure (Bar a , A / C) is 1 / 1, and the electrochemical impedance spectroscopy (EIS: Electrochemical Impedance Spectroscopy, Ω) is measured under the conditions of cell temperature 65℃, SR (A / C) is 1.5 / 2.0, RH (A / C) is 50 / 50 (%), working pressure (Bar a , A / C) is 1 / 1. SR is the stoichiometric ratio, A / C is the anode / cathode, and the ratio is used to express the amount of fuel supplied to each electrode based on the stoichiometric ratio.
[0127] from Fig. 9 and Fig.10 It can be seen that the membrane-electrode assembly manufactured in Example 1 forms a catalyst layer after controlling surface defects, so that the interface resistance between the polymer electrolyte membrane and the electrode is lower, and has excellent battery cell performance compared with the membrane-electrode assembly manufactured in Comparative Example 1.
[0128] The preferred embodiments of the present invention are described in detail above, but the above embodiments are presented as specific examples of the present invention, and the present invention is not limited thereto. The scope of rights of the present invention is defined in the appended claims, and various modifications and improvements made by those skilled in the art using the basic concepts of the present invention also fall within the scope of rights of the present invention.
[0129] Description of Reference Numerals
[0130] 10: Sprayer
[0131] 11: Solvent
[0132] 20: Heat and Pressure
[0133] 30, 30': Catalyst layer
[0134] 50: Polymer electrolyte membrane with controlled surface defects
[0135] 51: Polymer electrolyte membrane with surface defects
[0136] 52: Interface
[0137] Industrial Applicability
[0138] The present invention relates to a method for manufacturing a polymer electrolyte membrane and a membrane-electrode assembly, which can prevent the polymer electrolyte membrane from deteriorating while controlling the surface of the polymer electrolyte membrane with physical defects to be uniform, thereby reducing the interface resistance between the polymer electrolyte membrane and the electrode, obtaining excellent battery cell performance and improving the physical stability of MEA under long-term operation.
Claims
1. A method for manufacturing a polymer electrolyte membrane, comprising: A step of applying a solvent to a polymer electrolyte membrane having defects on its surface to swell the polymer electrolyte membrane; and A step of applying heat and pressure to the swollen polymer electrolyte membrane.
2. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The solvent includes water, alcohol, an organic solvent or a combination thereof.
3. The method for producing a polymer electrolyte membrane according to claim 2, wherein: The solvent is a mixed solvent including more than 0 wt % and less than 100 wt % of water and more than 0 wt % and less than 100 wt % of alcohol.
4. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The method of applying the solvent to the polymer electrolyte membrane includes spraying, steam spraying, or a combination thereof.
5. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The swelling step is performed for 1 second to 30 seconds.
6. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The length of the polymer electrolyte membrane after swelling increases by 1% to 20% compared with the length before swelling.
7. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The thickness of the polymer electrolyte membrane after swelling increases by 1% to 20% compared with the thickness before swelling.
8. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The step of applying heat and pressure is performed for 1 second to 30 seconds.
9. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The step of applying heat and pressure is performed at a temperature of about 20% of the intrinsic glass transition temperature (Tg) of the polymer electrolyte membrane.
10. The method for producing a polymer electrolyte membrane according to claim 9, wherein: The step of applying heat and pressure is performed at a temperature of 110°C to 130°C.
11. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The step of applying heat and pressure is performed by applying 50 kg / cm 2 Up to 200kg / cm 2 pressure to carry out.
12. The method for producing a polymer electrolyte membrane according to claim 1, wherein: The degree of degradation of hydrogen ion conductivity of the polymer electrolyte membrane before and after the step of applying heat and pressure is less than 5%.
13. A method for manufacturing a membrane-electrode assembly, comprising: A step of coating a composition for forming a catalyst layer on one or both surfaces of a polymer electrolyte membrane produced by the method according to claim 1.